Smart Self-Coherent Optical Communication for Short Distances - Nadimi Goki, Pantea; Imran, Muhammad; Cavaliere, Fabio; Potì, Luca (Frontiers in Communications and Networks, 2022)
We proposed and investigated a high-performance, energy-efficient, low-cost self-homodyne coherent detection transmission (SHCDT) system for the 5G access network segment assuring high capacity and light DSP at the same time, avoiding the local oscillator for detection. The system implementation is based on a code-based spectral shaping at the transmitter and carrier extractor at the receiver. In the Self-homodyne coherent system, a continuous wave carrier is transmitted together with the modulated signal. After transmission, at the receiver, the carrier is extracted and used as the local oscillator (LO) to prevent frequency offset with respect to the transmitted signal, and phase noise, resulting in a decrease in the digital signal processing (DSP) complexity. Transmission results indicate that even a low portion of residual LO on the transmitted signal at the receiver side can lead to an increase in the signal-to-noise ratio (OSNR) penalty. Consequently, applying a proper technique to separate the unmodulated carrier and the modulated signal is the main key to the system performance. We evaluated the self-homodyne coherent system performance through numerical analysis and experimental validation. The performance of the proposed self-coherent system, employing a narrow bandwidth Fabry-Perot filter for optical carrier extraction, is evaluated experimentally on a 28Gbaud dual-polarization 16QAM transmission system considering different code block lengths for signal spectral shaping through bit-error-rate (BER) measurements.